Genetic diversity in rumex nervosus vahl from Sarawat Mountains of Saudi Arabia (Bangladesh Journal of Botany, 2025)
This study assessed the genetic diversity of Rumex nervosus in southern Saudi Arabia using RAPD, ISSR, and combined RAPD-ISSR markers. A total of 218 RAPD and 211 ISSR bands were produced, with polymorphism rates of 47.7% and 63.5%, respectively. The highest polymorphism was recorded in primer OPE-3 (67.5%) for RAPD and UBC 826 (83.8%) for ISSR. Dendrogram analysis revealed distinct clusters with varying linkage distances, reflecting genetic relationships shaped by geographic proximity and ecological adaptation. The highest genetic similarity was observed between Bahat Rabiea and Alssawda (84.9% RAPD), Bahat Rabiea and Alothrban (82.9% ISSR), and Tabab and Bahat Rabiea (100% RAPD-ISSR). Conversely, the lowest similarity (16.7% RAPD-ISSR) occurred between Abha and Tabab, and Abha and Bahat Rabiea, indicating strong genetic divergence. These findings confirm that geographic isolation and genetic factors influence population structure, providing valuable insights for conservation, genetic resource management, and evolutionary and ecological research in the region.Bangladesh J. Bot. 54(3): 537-545, 2025 (September)